A study on coordinators AND, BUT, OR as cohesive devices - Võ Thị Thao Ly.; Trần Hữu Mạnh, Assoc.prof.Dr. (Hà Nội : Đại học Ngoại ngữ Hà Nội, 1999)
This thesis presents a study on coordinators AND, BUT, OR as cohesive devices.
Keywords: Anh ngữ; English thesis; Luận văn Anh ngữ; English coordinators; Cohesive devices; English linguistics -- Usage